IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS 4 DI MADRASAH IBTIDAIYAH NEGERI 1 JOMBANG - Fathur Rofi'i; Mishbahush Shudur; Misbah Bahauddin Faqih (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2024)
This study aims to determine the implementation and factors related to the implementation of the Independent Curriculum in the subject of Islamic Cultural History in class 4 of State Elementary School 1 Jombang. This study uses a qualitative descriptive approach. The data sources were obtained from interviews, observations and documentation, the technical data analysis used the Miles and Huberman model, namely: data reduction, data presentation and drawing conclusions. The results of this study indicate that: The implementation of the Independent Curriculum in the Subject of Islamic Cultural History in Class 4 of State Elementary School 1 Jombang has been carried out well, this is because there is good learning planning from Islamic Cultural History teachers and the ability to compile and implement the Independent Curriculum teaching module. The supporting factors are learning planning by teachers, motivation of the Principal and parents of students. While the inhibiting factors are the lack of interest, talent, student motivation, facilities and infrastructure and understanding of parents of students..